Respuesta :
Answer:
The correct answer is A. 5(x + 3)(x - 3)
Step-by-step explanation:
In order to solve this, we start by pulling out the greatest common factor.
5x^2 - 45
5(x^2 - 9)
Now we can use the difference of two squares to factor the rest of the equation.
5(x + 3)(x - 3)
Answer:
A. 5(x + 3)(x - 3)
Step-by-step explanation:
Given equation is,
[tex]5x^2-45[/tex]
[tex]=5x^2-5\times 9[/tex]
[tex]=5(x^2-9)[/tex]
[tex]=5(x^2-(3)^2)[/tex]
[tex]=5(x+3)(x-3)[/tex] ( a² - b² = (a+b)(a-b) )
Since, further factorization is not possible,
Hence, the required factored form of the given expression is,
[tex]5(x+3)(x-3)[/tex]
Option A is correct.